Sejarah dan Perkembangan Bersalawat Menggunakan Seni Bermain Beatbox Periode 2015-2020 - Agil Rizka Azka Azkia (UIN Sunan Gunung Djati Bandung, 2022)
Reading salawat is one of our practices and appreciation to Rasulullah SAW. Nowadays reading salawat is not only a rewarding practice, but it has also started to become a culture and a competition. This culture is also associated with art that has developed quite recently, namely using beatbox art, namely art that focuses on producing rhythmic sounds and drum beats, as well as imitation of other sounds through human speech organs. This study aims to find out the history of the emergence of salawat culture with beatbox art which has begun to develop today. The method used in this study is a qualitative method, namely by collecting data through literature, documentation, and interviews. Data analysis techniques were carried out using heuristic, criticism, interpretation and historiography methods. This research resulted in the finding that the art of praying using the beatbox version is quite effective in attracting the attention of young people in increasing love for the Prophet Muhammad.